2012
DOI: 10.1590/s1808-16572012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco associados à infecção pelo Herpesvírus Bovino Tipo 1 em rebanhos bovinos leiteiros da região Amazônica maranhense

Abstract: RESUMOO presente estudo teve como objetivo determinar a frequência e os fatores de risco para a infecção pelo Herpesvírus Bovino Tipo 1 (BoHV-1) em fêmeas bovinas leiteiras na região Amazônica maranhense. Amostras de soro de animais não vacinados contra o BoHV-1 e provenientes de 40 propriedades foram submetidas à técnica de ELISA indireto. Em cada propriedade avaliada, aplicou-se ainda um questionário epidemiológico para investigar os fatores de risco que poderiam estar associados à infecção pelo vírus. Das 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
(3 reference statements)
3
1
0
3
Order By: Relevance
“…The finding of this study corroborates that one obtained by BEZERRA et al (2012a), that when investigating dairy cattle in the Amazon region of Maranhão the presence of veterinary assistance as a protection factor was identified (OR = 0.37) for the occurrence of viral infection, with significant statistical association (p < 0.05). Similarly, SOUSA et al (2013) also verified the absence of veterinary assistance as a risk factor (OR = 7,714) for increased exposure to the agent (p < 0.05).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The finding of this study corroborates that one obtained by BEZERRA et al (2012a), that when investigating dairy cattle in the Amazon region of Maranhão the presence of veterinary assistance as a protection factor was identified (OR = 0.37) for the occurrence of viral infection, with significant statistical association (p < 0.05). Similarly, SOUSA et al (2013) also verified the absence of veterinary assistance as a risk factor (OR = 7,714) for increased exposure to the agent (p < 0.05).…”
Section: Resultssupporting
confidence: 91%
“…All of the eight investigated properties presented positive animals, and the prevalence distribution by property ranged from 43.3 to 86.2% (Table 1). Similar results were verified by BEZERRA et al (2012aBEZERRA et al ( , 2012b in Maranhão; both studies similarly found seropositive animals for BoHV-1 in all analyzed properties. According to ACKERMANN;ENGELS (2006), once the animal is infected by the alphaherpesvirus, it becomes a carrier and source of infection, which endangers the health of other susceptible animals.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, these results indicate that BoHV-1 is broadly disseminated in the region, which reinforces the possibility of these animals acting as sources of infection, mainly when dealing with animals with latent infection, which may disseminate the virus throughout their lives (BEZERRA et al, 2012). For BVDV, the positivity rate found was 8.8%, similar to the results found by Martins et al (2012) in the State of São Paulo (12.9%) and Scheffer (2013) in Rio Grande do Sul (10.8%).…”
Section: Resultssupporting
confidence: 52%
“…Brasil (BEZERRA et al, 2012), assim como a prevalência de infecções causadas pelo herpesvírus BoHV-5 (COLODEL et al, 2002;RISSI et al, 2006;SALVADORE;LEMOS;RIET-CORREA, 1998).…”
Section: Snunclassified